Effect of cutting age and auxin concentration on growth of pinto peanut (Arachis pintoi) - Muntoyib, Junaidi (Holistic: Journal of Tropical Agriculture Sciences, 2024)
Background: Pinto peanuts (Arachis pintoi) are known as versatile cover crops for soil conservation, biomulch, and ornamental plants. These leguminous plants rarely produce seeds, so they are commonly propagated vegetatively, resulting in low efficiency of seedling production and availability of cuttings. The aim of this study was to determine the effect of cutting age and auxin application on the growth of pinto peanut. Methods: This experiment used a complete randomized block factorial design. The first factor was the age of the cuttings (stolons) with three levels (young, intermediate, old). Each cutting had three nodes, with young cuttings measured from the tip, intermediate cuttings measured from the fourth node, and old cuttings measured from the seventh node. The second factor was the concentration of the commercial auxin product ROOTONE F (0 ppm, 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm). Findings: The results showed that the difference in cutting age significantly affected the number of leaves (at 10 and 50 days after planting), plant length (at 10 to 50 days after planting), number of branches (at 30 to 50 days after planting), and canopy area. Differences in auxin concentration only significantly affected plant length from 10 to 30 days after planting. The interaction between cutting age and auxin concentration was significant only for the number of leaves at 10 to 20 days after planting and plant length at 50 days after planting. Conclusion: The highest values for the observed parameters were consistently obtained by intermediate cuttings followed by tip cuttings, which are therefore recommended as planting material for pinto peanut propagation. Novelty/Originality of this article: This study uniquely determined the effectiveness of pinto peanuts cuttings based on internode length, revealing that intermediate cuttings are the best material for its propagation, especially when treated with specific auxin concentrations, consistently outperformed tip and old cuttings in promoting optimal growth, offering a practical strategy to enhance vegetative propagation efficiency.